Una misión educativa - Brown, Ofelia (2005)
This case study describes an initiative by a computer engineer to develop an innovative teaching method. The company providing financial support has as their sole motivation the altruistic purpose of improving education in Peru. After enacting the program, the people involved decided to form a non-profit association in order to collect donations and assure the resources that will allow the project’s expansion. The story unfolds in the city of Lima, Peru, in May of 2005.